Role of molecular adsorbent recirculating system in methotrexate-induced acute liver failure: a case report and literature review - Corbisier, T.; Von Bueren, André O.; Breunis, W.B.; Grazioli, S. (Frontiers in Pediatrics, 2024)
We describe a 14-year-old girl with osteosarcoma who was treated with high dose methotrexate (12g/m2). Twenty-four hours after the infusion, her plasma methotrexate concentration was elevated at 937 μmol/L (normal < 10 µmol/). She exhibited severe signs of methotrexate toxicity, including encephalopathy, acute liver failure, and acute kidney injury. The patient underwent extracorporeal epuration treatment for methotrexate prior to regaining normalized renal and hepatic function.In this case report, we describe severe and rare adverse effects secondary to methotrexate administration and the efficacity of MARS (Molecular Adsorbent Recirculating System) and CVVHDF (Continuous Veno-Venous Hemodiafiltration) to recover from multiple organ failure.